The use of dried cerebrospinal fluid filter paper spots as a substrate for PCR diagnosis of the aetiology of bacterial meningitis in the Lao PDR. (6th June 2013) - Elliott, I.; Dittrich, S.; Paris, D.; Sengduanphachanh, A.; Phoumin, P.; Newton, P. N.; Drancourt, M.
Abstract We investigated whether dried cerebrospinal fluid (CSF) conserved on filter paper can be used as a substrate for accurate PCR diagnosis of important causes of bacterial meningitis in the Lao PDR. Using mock CSF, we investigated and optimized filter paper varieties, paper punch sizes, elution volumes and quantities of DNA template to achieve sensitive and reliable detection of bacterial DNA from filter paper specimens. FTA Elute Micro Card™ (Whatman, Maidstone, UK) was the most sensitive, consistent and practical variety of filter paper. Following optimization, the lower limit of detection for Streptococcus pneumoniae from dried mock CSF spots was 14 genomic equivalents (GE)/μL (interquartile range 5.5 GE/μL) or 230 (IQR 65) colony forming units/mL. A prospective clinical evaluation for S. pneumoniae, S. suis and Neisseria meningitidis was performed. Culture and PCR performed on fresh liquid CSF from patients admitted with a clinical diagnosis of meningitis (n = 73) were compared with results derived from dried CSF spots. Four of five fresh PCR‐positive CSF samples also tested PCR positive from dried CSF spots, with one patient under the limit of detection. In a retrospective study of S. pneumoniae samples (n = 20), the median (IQR; range) CSF S. pneumoniae bacterial load was 1.1 × 104 GE/μL (1.2 × 105; 1 to 6.1 × 106 DNA GE/μL). Utilizing the optimized methodology, we estimate an extrapolated sensitivity of 90%, based on the range of CSF genome counts found in Laos. Dried CSF filter paper spots could potentially help us to better understand the epidemiology of bacterial meningitis in resource‐poor settings and guide empirical treatments and vaccination policies.